Multiphysics simulations of thermoelectric generator modules with cold and hot blocks and effects of some factors. (September 2017) - Li, W.; Paul, M.C.; Montecucco, A.; Siviter, J.; Knox, A.R.; Sweet, T.; Gao, M.; Baig, H.; Mallick, T.K.; Han, G.; Gregory, D.H.; Azough, F.; et al.
Abstract: Transient and steady-state multiphysics numerical simulations are performed to investigate the thermal and electrical performances of a thermoelectric generator (TEG) module placed between hot and cold blocks. Effects of heat radiation, leg length and Seebeck coefficient on the TEG thermal and electrical performances are identified. A new correlation for the Seebeck coefficient with temperature is proposed. Radiation effects on the thermal and electric performances are found to be negligible under both transient and steady-state conditions. The leg length of the TEG module shows a considerable influence on the electrical performance but little on the thermal performance under transient conditions. A nearly linear temperature profile on a leg of the TEG module is identified. The temperature profile of the substrate surfaces is non-uniform, especially in the contacted areas between the straps (tabs) and the substrates.